Neurofibromatosis Type 1 with Subacute Sclerosing Panencephalitis: A Rare Coexistence - Safa Barış; Dilfuza Fakhratova; Mine Özdil; Serap Uysal (Güncel Pediatri)
Neurofibromatosis type 1 is an autosomal dominant disorder with variable expressivity. The major diagnostic features are cafe-au-lait spots, neurofibromas, Lisch nodules of the iris, optic glioma, axillary freckling and bony dysplasia. Affected patients develop benign and malignant tumors with increased frequency. The major cause of death is malignancy including brain and malignant peripheral nerve sheath tumors. Subacute sclerosing panencephalitis is a disorder characterized by progressive regression in behavior, myoclonic seizures and finally death. We report a 9 year old girl with Neurofibromatosis Type 1, observed to have myoclonic seizures and progressive deterioration of speech, finally diagnosed as subacute sclerosing panencephalitis. Because it is not previously reported in the literature, we aimed to report a Neurofibromatosis Type 1 patient with Subacute sclerosing panencephalitis. (Journal of Current Pediatrics 2008; 6: 83-5)